A critical examination of the policy and practice of the Methodist Church of Southern Africa regarding the readmission of ministers who have resigned or who have been discontinued as a result of divorce - Van Niekerk, Ockert (Rhodes University, Faculty of Divinity, Department of Divinity, 1999)
The scope and purpose of this research is the examination of the theology and practice of the Methodist Church of Southern Africa in matters relating to marriage, divorce and remarriage in ministry. The theology of the Methodist Church of Southern Africa is based on its understanding of the scriptural injunctions on these matters and the Wesleyan tradition. These are examined in some detail as is the one paper in existence produced by the church on the subject. This is the report by a committee appointed by the Conference of the Methodist Church of Southern Africa, convened by Dr Donald Cragg; M.A. (OX ON) D.Phil. (OXON). This document is referred to in this thesis as The Cragg Document. Section One of this thesis deals with research into the theology of the church. The practice of the church is examined using the recently completed study by the writer of the decided cases of the church in all disciplinary matters dealt with by Conference from 1957 to 1997. These were compiled from the existing record of Conference proceedings kept in the Methodist Connexional Office in Durban. This case precedent is included in a larger work also recently completed by the writer, namely A Handbook/or Disciplinary Committees. This book is in the process of being published by the church. Section two of this work deals with research into the practice of the church. The conclusions drawn at the end of this paper include a possible model for ministry to ministers and their families in the area of marriage and family enrichment and pastoral assistance to families in crisis. This thesis includes qualitative research into the aforesaid practice and procedure of the church in these matters and it is submitted that the conclusions drawn and the model posed in the concluding chapters can be of value to the church as it seeks to deal of the problem of an increasing number of ministers suffering the breakup of their homes and going through the trauma of divorce.
Keywords: Uncatalogued